The Prevalence of Trauma Among Participants in a Juvenile Mental Health Court - Zettler, Haley R. (Criminal justice and behavior, 2024)
There is evidence that youth in the justice system are more likely to experience trauma and mental health problems than the general population. Trauma histories may exacerbate mental health problems, and mental health problems may increase the likelihood of continued offending. While prior research has examined the effects of adverse childhood experiences (ACEs) on recidivism, it has yet to consider the prevalence of trauma among youth in a juvenile mental health court. Data from an urban juvenile mental health court (N = 203) was used to assess the prevalence of ACEs. The average ACE score of participants was 3.6% and 46% had a high ACE score. Furthermore, those who did not complete the program and/or were rearrested following participation had significantly higher ACE scores. Controlling for other factors, ACEs were not significantly associated with program noncompletion or rearrest. Policy implications surrounding trauma-informed practices are provided.